2010
DOI: 10.1029/2010gl043538
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and thresholds of biome shifts in Amazonia

Abstract: [1] We examine potential critical thresholds for biome shift in the Amazonian tropical forest by forcing a potential vegetation model with prescribed climate anomalies and projections from global and regional climate models and different levels of CO 2 fertilization effect under the SRES A2 scenario . The results indicate that tropical forests might be replaced by seasonal forests or savanna over eastern Amazonia with temperature increases of 2-3°C (4-5°C), when CO 2 fertilization effect is not considered (par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…It has been suggested that there may be thresholds or "tipping points" that should not be transgressed for the maintenance of the Amazonian tropical forests: 40% of area deforested, beyond which forest loss causes climate impacts that cause further forest loss (91); global warming of 3°C to 4°C may also lead to a similar tipping point (106,107). Although the existence of these tipping points still requires further research, interaction between climate change due to global warming and due to large-scale deforestation may make them more likely.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that there may be thresholds or "tipping points" that should not be transgressed for the maintenance of the Amazonian tropical forests: 40% of area deforested, beyond which forest loss causes climate impacts that cause further forest loss (91); global warming of 3°C to 4°C may also lead to a similar tipping point (106,107). Although the existence of these tipping points still requires further research, interaction between climate change due to global warming and due to large-scale deforestation may make them more likely.…”
Section: Significancementioning
confidence: 99%
“…Controlled fire experiments carried out in the transition forests of northern Mato Grosso showed great incidence of lianas and tree mortality, supporting, according to the authors (71), the likelihood of "savannization" of parts of the Amazon. Depending on the scale, these changes could ultimately drive changes in the local climate, pushing the ecosystem toward a different forest−climate equilibrium state (159), that is, the one where most of the tropical forests in southern, southwestern, and southeastern Amazon are replaced by degraded savannas as predicted by models (91,106,158,160). Evidence that the relationship between degraded forest, regional climate change, and a change in the equilibrium would lead to a tipping point in the Amazon region is described as a medium-confidence likelihood (161), but is already being observed in the Xingu basin (71).…”
Section: Impacts Of Anthropogenic Drivers Of Change In the Amazonmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors highlighted that partial deforestation can lead to an increase in precipitation locally, whilst increasing deforestation can lead to drier conditions. In terms of future projections, Salazar, L.F. et al [23] performed simulations using a regional climate model from the Centro de Previsão de Tempo e Estudos Climáticos nested with the Potential Vegetation Model (CPTEC-PVM2.0) and different prescribed annual anomalies precipitation and temperature added to the observed climatology, and different levels of CO 2 fertilization effects under emission scenario A2. These simulations indicate that: (a) tropical forests might be replaced by seasonal forests or savanna over eastern Amazonia with temperature increases of 2-3 • C, when the CO 2 fertilization effect is not considered; (b) a decrease in precipitation greater than 30% may shift tropical forest to drier biomes in southeastern Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, trees have been colonizing a well-established, stable and highly diverse grass dominated ecosystem in the study site (Behling & Pillar, 2007), which is fundamentally different from what has been observed in boreal systems, where due to low or no resistance from resident vegetation, forest expansion occurs at much faster rates. In contrast to the above results predicting forest expansion over savanna, Salazar and Nobre (2010) assume that tropical forests might be replaced by seasonal forests or savanna over eastern Amazonia with temperature increases of 2-5 °C, when CO 2 fertilization effect is not or partially considered. A precipitation decrease greater than 30% would also trigger the shift from tropical forest to drier biomes, such as savanna and shrubland in southeastern Amazonia.…”
Section: Savannization and Forest Encroachmentmentioning
confidence: 92%